2020
DOI: 10.1016/j.psj.2019.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Dietary l-arginine supplementation ameliorates inflammatory response and alters gut microbiota composition in broiler chickens infected with Salmonella enterica serovar Typhimurium

Abstract: This study was conducted to investigate the effects of dietary arginine ( Arg ) supplementation on the inflammatory response and gut microbiota of broiler chickens subjected to Salmonella enterica serovar Typhimurium. One hundred and forty 1-day-old Arbor Acres male birds were randomly assigned to a 2 × 2 factorial arrangement including diet treatment (with or without 0.3% Arg supplementation) and immunological stress (with or without S. typhimurium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 63 publications
10
57
0
Order By: Relevance
“…challenge, eliciting an immune response composed mainly of mononuclear cells (T-lymphocytes) and heterophils [ 36 , 37 , 38 ]. Furthermore, we found that supplementation with FDA slightly reduced the severity of the lesions in the treated group, which paralleled what has been reported after supplementation with arginine in the jejunum of broilers [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…challenge, eliciting an immune response composed mainly of mononuclear cells (T-lymphocytes) and heterophils [ 36 , 37 , 38 ]. Furthermore, we found that supplementation with FDA slightly reduced the severity of the lesions in the treated group, which paralleled what has been reported after supplementation with arginine in the jejunum of broilers [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…These findings are in line with studies assessing S . Typhimurium-induced histopathology in chickens [ 29 , 34 , 35 ]. The inflammatory infiltrate observed was predominantly composed of lymphocytes and severely affected the duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diet has a significant impact (estimated at 57%, compared with 12% for genetic factors) on gut microbial community structure ( Tomasello et al, 2014 ). Up to now, many nutritional factors have been reported to affect gut microbial community structure, including resistant starch ( Warren et al, 2018 ; Zhou et al, 2020 ), fat ( De Lartigue et al, 2011 ; Kim et al, 2019 ; Zhou et al, 2020 ), fructose ( Do et al, 2018 ), glucose ( Do et al, 2018 ), casein ( Masarwi et al, 2018 ; Pi et al, 2020 ), and arginine ( Zhang et al, 2018 , 2020 ). The novelty of the present work lies in the comprehensive characterization of gut microbial communities in Chinese perch after being fed with different contents of gelatinized starch diets and their correlation with gut health.…”
Section: Discussionmentioning
confidence: 99%